2012
DOI: 10.1109/jproc.2012.2189788
|View full text |Cite
|
Sign up to set email alerts
|

Wireless Myths, Realities, and Futures: From 3G/4G to Optical and Quantum Wireless

Abstract: This paper evaluates both the operational third-generation (3G) as well as the emerging fourth-generation (4G) wireless systems and investigates new technologies that might transpire and change things in the future.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
270
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 358 publications
(274 citation statements)
references
References 147 publications
2
270
0
2
Order By: Relevance
“…6 it can be observed that the polynomial g 1 (D) requires the fewest decoding iterations to reach the top right corner at [1,1] for both SNR values. Since g 2 (D) requires fewer decoding iterations to reach the [1,1] corner, we may conclude that it outperforms g 3 (D). This shows that the EXIT chart based performance prediction agrees with the MItrends of Fig.…”
Section: Simulation Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…6 it can be observed that the polynomial g 1 (D) requires the fewest decoding iterations to reach the top right corner at [1,1] for both SNR values. Since g 2 (D) requires fewer decoding iterations to reach the [1,1] corner, we may conclude that it outperforms g 3 (D). This shows that the EXIT chart based performance prediction agrees with the MItrends of Fig.…”
Section: Simulation Resultsmentioning
confidence: 94%
“…In the current era of mobile communication android phones, tablets, notebooks and laptops are in great demand throughout the world, which has resulted in an exponential increase of data traffic [1,2]. Hence the information transmission over the channel should be as bandwidth-efficient as possible [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a truly revolutionary paradigm shift [1], [2], wireless technology relying on radio waves has become an integral part of our everyday life, facilitating basic services, such as making a phone call or sending a message, as well as nearfield-communication-aided mobile payment. The radio waves occupy the 3 kHz∼300 GHz electromagnetic band, which has been widely used for communication purposes.…”
Section: Introductionmentioning
confidence: 99%